The Toilet Training Habits Formation Strategy for Children Aged 4-5 Years - Azizah Zein; khadijah Khadijah (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2025)
Toilet training habits are one of the essential life skills that should be instilled early to develop children's independence and responsibility in daily life. This study aims to analyze the strategies used to build toilet training habits implemented in early childhood education institutions. The method used is qualitative research with a case study approach. Data were collected through observation, interviews with teachers, and documentation of children's routine activities. The findings reveal that the toilet training strategy is carried out in a structured and consistent manner, beginning with introducing toilet etiquette according to religious teachings, training children to queue, and fostering responsibility for their personal belongings. Teachers play an active role as behavior models through direct practice and routine verbal communication. Despite challenges such as environmental differences between home and school toilets and limited parental understanding, the implementation of toilet training remains effective due to strong collaboration among educators. This study concludes that the success of toilet training highly depends on repeated habituation, active teacher involvement, and synergy with parents. The results of this study contribute to the development of independent behavior strategies for early childhood based on religious values and applicable pedagogical approaches.